APLIKASI MOBILE “MOGIZ” UNTUK MONITORING STATUS GIZI - Endri Yuliati; Yunita Indah Prasetyaningrum; Dwi Miyanto (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
“MOGIZ” Mobile Application for Monitoring Nutritional StatusBackground: many mobile applications for health have been developed, but only a few have the development process based on user needs. Objective: the purpose of this research is to produce an user friendly, acceptable, and beneficial mobile application for many people. Methods: the MoGiz android application is developed with a user-centered design method using the Java software development kit 8, android studio, visual studio code, and flutter framework. MoGiz consist of six main menus: 1) Measurement method, 2) Check nutritional status, 3) Measurement history, 4) Consultation, 5) Advice, and 6) About MoGiz. In the first menu, user can read articles about how to measure some body parameters correctly and view videos. In the second menu, user can input their weight and height, upper arm circumference, waist and hip circumference and then find out the interpretation. Results: MoGiz has tried to include gamification by giving points to each user activity such as measuring nutritional status, answering quizzes and sharing the results of measuring nutritional status to social media. If the points meet the limit, it can be exchanged for rewards. Conclusion: MoGiz has been developed for various age groups as a guide for the community to assess nutritional status independently. In addition, this application also provides nutrition and health information for user which is expected to encourage people's habits to behave in a healthy and nutritionally balanced manner.